ADIKSI NARKOBA DI PANTI REHABILITASI DALAM PERSPEKTIF KONSELING ISLAM - Arifani Ridwan; Hadi Warsito Wiryosutomo; Budi Purwoko (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Drug addiction is a serious problem in today's society. In this context, the effectiveness of Islamic counseling has emerged as one of the approaches used to help people deal with drug addiction and the legal consequences that may be associated with it. This approach combines behavioristic principles that focus on changing behavior with Islamic religious values and teachings that teach ethics, morality, and social responsibility. In the counseling process, the main focus is on changing behavior through identifying and eliminating negative behaviors related to drug addiction effectively providing holistic and integrated results. Apart from helping drug addicts overcome drug addiction and negative behavior changes, this approach also helps them gain a deeper understanding of Islamic values, ethics and social responsibility. Thus, this counseling provides a strong spiritual foundation for addicts to recover, avoid falling back into drug addiction, and build a life that is more in line with Islamic values.